2016
DOI: 10.1021/acsbiomaterials.6b00258
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Porous Cell-Laden Hydrogel Constructs for Potential Applications in Cartilage Tissue Engineering

Abstract: Hydrogels are particularly attractive as scaffolding materials for cartilage tissue engineering because their high water content closely mimics the native extracellular matrix (ECM). Hydrogels can also provide a threedimensional (3D) microenvironment for homogeneously suspended cells that retains their rounded morphology and thus facilitates chondrogenesis in cartilage tissue engineering. However, fabricating hydrogel scaffolds or cellladen hydrogel constructs with a predesigned external shape and internal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 65 publications
1
82
0
Order By: Relevance
“…In some tissue engineering applications, such as peripheral nerve (Ning et al, 2016), bone (Naghieh et al, 2016b), and articular cartilage (You et al, 2016b) regeneration, scaffolds undergo compressive force exerted by over-and underlying tissues in one direction. In such cases, the compressive elastic modulus is important in one direction while the scaffold mechanical behavior in other directions might be different; indeed, bioprinted scaffolds are not isotropic (Olubamiji et al, 2016).…”
Section: Figure 2 the Model Developed To Represent The Structure Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In some tissue engineering applications, such as peripheral nerve (Ning et al, 2016), bone (Naghieh et al, 2016b), and articular cartilage (You et al, 2016b) regeneration, scaffolds undergo compressive force exerted by over-and underlying tissues in one direction. In such cases, the compressive elastic modulus is important in one direction while the scaffold mechanical behavior in other directions might be different; indeed, bioprinted scaffolds are not isotropic (Olubamiji et al, 2016).…”
Section: Figure 2 the Model Developed To Represent The Structure Ofmentioning
confidence: 99%
“…Among various divalent ions, Ca 2+ ions facilitate superb printability for alginate precursors while maintaining reasonable cell viability (Swioklo et al, 2016). Mechanically stable alginate scaffolds can be successfully fabricated using CaCl2 solution at higher concentrations (You et al, 2016a), but the incorporated cells can be adversely affected (Cao et al, 2012). Therefore, extruding the alginate precursor into a lower concentration CaCl2 solution has been recommended to limit effects on cell viability (Tabriz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The submerged-in-crosslinker cell printing process, referred to as drop-on-demand printing, has been applied to the inkjet [39,40] , laser-assisted [41] , and extrusion-based [42,43] cell printing processes to build 3D structures with relatively low-viscosity bioinks. Xu et al [39] and Boland et al [40] built the drop-on-demand printing apparatus shown in , which uses a layer-by-layer-sinking plate in the crosslinker-filled chamber, and the alginate-based bioink was printed on the surface of the crosslinking liquid.…”
Section: Cell Printing With Modified Crosslinking Processesmentioning
confidence: 99%
“…applied a similar method to the laser-assisted cell printing process, which contains the same limitations in printing 3D structures, and they were able to fabricate a 3D structure with a height of 9.5 mm. Conversely, You et al [42] fabricated a 3D lattice structure with cell-laden alginate hydrogel via an extrusion-based cell printing process with submerged crosslinking. They coated the surface of a printing plate, instead of using a lifting stage, and printed the bioink in a CaCl 2 solution to build a biaxially porous 3D scaffold, which created pores between the deposited layers.…”
Section: Cell Printing With Modified Crosslinking Processesmentioning
confidence: 99%
“…This precise positioning of multiple cell types in an organized manner can be achieved with 3D bioprinting [4]. Plenty of natural materials, such as gelatin [5,6], alginate [7][8][9], collagen [10,11], and synthetic materials like polycaprolactone (PCL) [12][13][14][15][16] and polyethylene glycol (PEG) [17][18][19][20][21][22], come in handy while printing a structure. Although the abovementioned natural materials are biocompatible, disadvantages such as mechanical instability, limited degradability, restricted cell proliferation, and differentiation challenged researchers to investigate more on natural materials [23][24][25].…”
Section: Introductionmentioning
confidence: 99%